Electrochemical Performance and Phase Transitions between 1.5 and 4.9 V of Highly-Ordered LiNi0.5Mn1.5O4 with Tailored Morphology: Influence of the Lithiation Method. Issue 1 (13th December 2016) - Mancini, M.; Gabrielli, G.; Axmann, P.; Wohlfahrt-Mehrens, M.
Abstract : We report about the electrochemical performance in the potential range 1.5 to 4.9 V of highly ordered, stoichiometric LiNi0.5 Mn1.5 O4 with spinel structure and tailored morphology. Structural and morphological parameters are optimized for obtaining maximum energy density in Li-ion cell applications. The effect of the discharge cutoff on the cathode capacity, cycling stability and coulombic efficiency is discussed. Li-rich structures with composition Li1+x Ni0.5 Mn1.5 O4 (0 < × < 1) obtained via electrochemical lithiation are investigated via ex-situ XRD and SEM analysis. The results are compared with those obtained via a chemical lithiation method, showing that the phase transition from cubic LiNi0.5 Mn1.5 O4 to tetragonal Li2 Ni0.5 Mn1.5 O4 occurs via a two-phase mechanism with no evidence of intermediate phases. The superior electrochemical performance of the synthesized cathode material is ascribed to its specific morphology that provides suitable properties for reduced side-reactions with the electrolyte and low impact of the volumetric changes during cycling.